STUDI PARTISIPASI KELOMPOK PETERNAK PADA USAHA TERNAK SAPI BALI - Yusuf Hasan; Suparmin Fathan; Nibras Karnain Laya; Yuriko Boekoesoe; Mohamad Ikbal Bahua; Fahria Datau (Gorontalo Journal of Equatorial Animals, 2022)
The purpose of this study was to determine the level of group participation in the Bali cattle business in Limehu village, Tabongo district, Gorontalo district. The research method used is a survey method by preparing primary and secondary data. Data were collected by observation and interviews with a questionnaire instrument. Determination of sampling is done at simple random, with a total of 59 respondents. The data obtained were analyzed using descriptive analysis, which was assisted by an ordinal scoring technique from the order of High, Medium, Low. The results of the analysis show that the level of farmer participation in Limehu Village, Tabongo District, Gorontalo Regency is in the good (high) category, with an average of 1167 with a total score of 3,501. The business contribution of 100% is still productive to the participation rate, 23% of education is still lacking for the participation rate, 20.33% or 3-4 head of livestock ownership is classified as a side business, 77.96% experience of raising 1-3 years is good but needs to be improved in the cattle business cut.